Two texts in the dialectal Arabic of Damascus - Berliches Ramos, Carmen (Anaquel de Estudios Árabes, 2011)
This paper contains two texts in the dialectal Arabic of Damascus (Syria), followed by an analysis and the Spanish translation thereof. The aim is to show the main characteristics of the modern language spoken amongst the young Damascenes.
Keywords: Arabic dialectology; Oriental dialects; Dialect of Damascus.